2020
DOI: 10.4103/ajns.ajns_193_19
|View full text |Cite
|
Sign up to set email alerts
|

Infraoptic course of anterior cerebral artery coexistence with double fenestration of proximal A2 segment of anterior cerebral artery with associated dysplastic anterior communicating artery aneurysm treated with stent-assisted coiling

Abstract: Infraoptic course of anterior cerebral artery coexistence with double fenestration of proximal A2 segment of anterior cerebral artery with associated dysplastic anterior communicating artery aneurysm treated with stent-assisted coiling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…11 Rarely, the A2 segment of the ACA can be associated with fenestration, and fenestration is often located at the beginning of the A2 segment. [12][13][14] Exceptionally, the AACA trunk can have a fenestration at the A2 segment beginning, as in our case. Intracranial arterial fenestration has an angiographical incidence of 0.3%-0.9% and is often observed in posterior circulation, unusually in anterior circulation.…”
Section: Discussionmentioning
confidence: 93%
“…11 Rarely, the A2 segment of the ACA can be associated with fenestration, and fenestration is often located at the beginning of the A2 segment. [12][13][14] Exceptionally, the AACA trunk can have a fenestration at the A2 segment beginning, as in our case. Intracranial arterial fenestration has an angiographical incidence of 0.3%-0.9% and is often observed in posterior circulation, unusually in anterior circulation.…”
Section: Discussionmentioning
confidence: 93%
“…Different authors reported cases of aneurysms associated with infraoptic ACAs [ 20 ]. These were found on the AComA or on the A1 or A2 segments of the ACA [ 4 , 5 , 7 , 8 , 13 , 18 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. An aneurysm on an infraoptic A1 segment of an azygos ACA was also reported [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fenestrations have been described in the A1 segment of the anterior cerebral artery, although the most frequently affected segment of the anterior circulation is the Anterior communicating artery (Acom) (Mamadaliev et al, 2019;Trandafilovic et al, 2021). As with all other vascular disorders, cerebral angiography is invaluable in their accurate diagnosis (Mahajan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The distal A1 segment is described as the most frequently associated with fenestrations in dissections of cadavers. Various theories have been reported to explain the association between aneurysms and fenestrations, including: Vascular wall weakness (Iwabuchi et al, 2018), and failure of fusion of the plexiform multi-channel network of vessels that develop into major arteries during fetal life (Krystkiewicz et al, 2021;Kwon et al, 2013;Mahajan et al, 2020;Makowicz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%